2012
DOI: 10.1097/sla.0b013e31824a36cc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Outcomes With Alvimopan in Clinical Practice

Abstract: On average, alvimopan-treated patients had a lower incidence of mortality and most incidents of morbidities. Length of stay, ICU use, and estimated cost were also lower with comparable readmissions. These results in patients outside the clinical trial setting include laparoscopic colectomy and demonstrate a potential association between acceleration of gastrointestinal recovery and improved early postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Finally, the large-scale report of alvimopan used in treatment of 3525 patients after open or laparoscopic bowel resection revealed that the administration of alvimopan reduced the length and costs of hospitalization [153]. Lower incidence of GI morbidity, mortality and intensive care unit (ICU) stay were also reported.…”
Section: Opioid System In Pathophysiological Conditions Of the Gi Tractmentioning
confidence: 99%
“…Finally, the large-scale report of alvimopan used in treatment of 3525 patients after open or laparoscopic bowel resection revealed that the administration of alvimopan reduced the length and costs of hospitalization [153]. Lower incidence of GI morbidity, mortality and intensive care unit (ICU) stay were also reported.…”
Section: Opioid System In Pathophysiological Conditions Of the Gi Tractmentioning
confidence: 99%
“…Good analgesia promotes early activities of patients, reduces complications, improves selfcare ability in daily life, and accelerates recovery. Early getting out of bed helps improve blood circulation throughout the body, can effectively reduce the occurrence of complications, such as deep vein thrombosis and pulmonary infection, promote patient recovery, shorten postoperative hospital stay, improve quality of life, and reduce economic pressure (14)(15)(16). Respiratory system management is an important part of ERAS and runs through the entire operation period.…”
Section: Eras Could Reduce the Occurrence Of Complications After Surgerymentioning
confidence: 99%
“…380–382 Most of the nonrandomized studies have shown modest benefits in favor of alvimopan for laparoscopic resection albeit within traditional care pathways. 383–385 Given the low quality of the available evidence, it may be difficult to justify the use and cost of alvimopan in laparoscopic surgery in the setting of an ERP.…”
Section: Postoperative Interventionsmentioning
confidence: 99%
“…[380][381][382] Most of the nonrandomized studies have shown modest benefits in favor of alvimopan for laparoscopic resection albeit within traditional care pathways. [383][384][385] Given the low quality of the available evidence, it may be difficult to justify the use and cost of alvimopan in laparoscopic surgery in the setting of an ERP. Urinary catheterization is routinely used in abdominal and pelvic colorectal surgery for intraoperative bladder decompression and monitoring urinary output.…”
Section: Sham Feeding (Ie Chewing Gum For ≥10 Min 3-4×mentioning
confidence: 99%